COVID-19 community care in Israel—a nationwide cohort study from a large health maintenance organization. (5th March 2021) - Shapiro Ben David, Shirley; Cohen, Daniella; Karplus, Rebekah; Irony, Angela; Ofer-Bialer, Gili; Potasman, Israel; Greenfeld, Orly; Azuri, Joseph; Ash, Nachman
Abstract: Background: Among the many medical challenges presented by the COVID-19 pandemic, management of the majority of patients in community outpatient settings is crucial. The aim of this study was to describe the characteristics and outcomes among confirmed COVID-19 cases who were managed at three settings: two outpatient settings and one inpatient. Methods: A retrospective database cohort study was conducted in a large Israeli Health Maintenance Organization. All COVID-19 cases diagnosed between 28 February 2020 and 20 July 2020 were included. Cases in the community settings were managed through a nationwide remote monitoring center, using preliminary telehealth triage and 24/7 virtual care. Outcome parameters included hospital admission, disease severity, need for respiratory support and mortality. Results: About 5448 cases, aged range 0–97 years, were enrolled; 88.7% were initially managed as outpatient either at home or in designated hotels, 3.1 and 2.1% of them, respectively, later required hospitalization. The main reason for hospitalization was dyspnea; 12 were diagnosed with severe disease; 56 patients (1.3%) died, five (0.1%) of whom were initially allocated to the outpatient settings. Conclusions: Care for appropriately selected COVID-19 patients in the community provides a safe and effective option. This can contribute to reducing the hospitalization burden, with no evidence of increased morbidity or mortality.